Research on coal wall failure and stability control technology of large coal seams with a soft and thick seam - Weibin Guo; Gang Wang; Yuhui Li; Dengfeng Chen (Energy Science & Engineering, 2024)
Abstract To address the issues of coal rib instability and high occurrence of roof falls in high extraction height fully mechanized coal mining of soft coal seams, this study comprehensively employs theoretical analysis, numerical calculations, and field industrial experiments. By analyzing the distribution characteristics of coal rib displacement and deformation instability zones under different mechanical parameters of soft coal seams, the instability mechanism of coal ribs in high extraction height mining of thick and soft coal seams is revealed, and corresponding stability control techniques for high extraction height coal ribs and supports are developed. The study shows that the stability of coal ribs in high extraction height mining fields of soft and thick coal seams decreases as the values of mechanical parameters decrease. In other words, the smaller the cohesion and deformation parameters of the coal body, the more prone the coal rib is to roof falls. By utilizing advanced deep‐hole static water infusion technology, the frequency of roof falls in extremely soft high extraction height working faces is reduced by 80%, the average depth of roof falls is decreased by 35%, and the average length of roof falls is reduced by 50%. The stability of the coal ribs is effectively improved.